Analisis Pemeriksaan CT Scan Abdomen Dengan Kontras Pada Klinis Ileus Obstruktif di Rumah Sakit Bhayangkara Makassar - Alifah Rizky Octavia; Ni Putu Rita Jeniyanthi; I Kadek Sukadana (Journal of Educational Innovation and Public Health, 2024)
The diagnosis of obstructive ileus is comfirmed by a CT Scan of the abdomen. The CT Scan of the Abdomen examination procedure with contrast in clinical obstructive ileus at Bhayangkara Hospital Makassar uses intravenous contrast injection. This study aims to analyze abdominal CT Scans with contrast in cases of obstruktive ileus and the contrast media injection technique used. This type of research is descriptive qualitative with a case study approach. This research was conducted at Bhayangkara Hospital Makassar. Data collection methods and were carried out by means of observation, interviews, and documentation. The results of this study show that the abdominal protocol, then pre contrast scanning is carried out. 50 ml of contrast is admistered intravenously. The abdominal CT Scan examination procedure with contras in cases of obstructive ileus at Bhayangkara Hospital Makassar only uses intravenous administration of contrast media because it is sufficient for diagnosis and the examination time is shorter.